Asthma is associated with enhanced thrombin formation and impaired fibrinolysis. Issue 7 (3rd May 2016) - Bazan‐Socha, S.; Mastalerz, L.; Cybulska, A.; Zareba, L.; Kremers, R.; Zabczyk, M.; Pulka, G.; Iwaniec, T.; Hemker, C.; Undas, A.
Summary: Background: There is evidence that altered blood coagulation and fibrinolysis are involved in the pathogenesis of asthma. Increased thromboembolic risk has been reported in asthmatics. Objective: To investigate whether enhanced thrombin generation and impaired fibrinolysis occur in asthmatics. Methods: Plasma thrombin generation profile together with a computational assessment of thrombin dynamics and fibrinolytic capacity expressed as clot lysis time (CLT) were determined in 164 consecutive patients with stable asthma and 72 controls matched for age, gender, weight and smoking. Results: Asthma patients had 20.2% increased endogenous thrombin potential (ETP), 41.4% higher peak thrombin concentration, 61% higher maximal prothrombin conversion rate, 15.5% faster rate of thrombin formation (all, P < 0.0001) and 10% lower thrombin decay capacity ( P = 0.0004) compared with controls. Asthmatics had also 14.4% longer CLT ( P = 0.001) associated with 21.3% higher plasminogen activator inhibitor‐1 (PAI‐1) ( P < 0.0001), and 13% higher plasma α2 ‐macroglobulin ( P = 0.0002). Using ETP and CLT above 75th percentile of the control values as the cut‐off levels, we found increased risks of enhanced thrombin generation and hypofibrinolysis in asthmatics, also after correction for potential confounders. ETP and CLT were associated inversely with forced expiratory volume in 1 s/vital capacity (FEV1 /VC) index, after adjustment for age and body mass index. Non‐allergic asthma ( n = 70, 42.6%) was characterized by 17.5% longer CLT ( P = 0.02), which positively associated with PAI‐1. Thrombin generation profile was not affected by allergy. Conclusion and Clinical Relevance: Asthma is associated with enhanced thrombin generation and impaired fibrinolysis, which might contribute to thromboembolic events in this disease.